Antibiotic Administration Routes and Oral Exposure to Antibiotic Resistant Bacteria as Key Drivers for Gut Microbiota Disruption and Resistome in Poultry - Zhou, Yang; Li, Yu; Zhang, Lu; Wu, Zuowei; Huang, Ying; Yan, He; Zhong, Jiang; Wang, Li-Ju; Abdullah, Hafiz M.; Wang, Hua H. (Frontiers in Microbiology, 2020)
Previous studies have identified oral administration of antibiotics and gut-impacting drugs as critical drivers for fecal antibiotic resistance (AR) and microbiome disruption in lab mice, but the practical implications of these findings have yet to be validated in hosts nurtured in conventional environment. Using ampicillin (Amp) as a way to extrapolate the general effect of antibiotics, this project examined the impact of drug administration routes on fecal microbiota and resistome using poultry raised in a teaching farm. AR genes were found to be abundant in the feces of young Leghorn chicks without previous antibiotic treatment. In chickens seeded with blaCMY-2+ Escherichia coli, 300 mg/kg body weight of Amp was orally administered for 5 days. This led to the fecal microbiota switching from Firmicutes occupied (95.60 ± 2.62 %) and Lactobacillus rich, to being dominated by Proteobacteria (70.91 ± 28.93%), especially Escherichia/Shigella. However, when Amp was given via muscle injection, Firmicutes was mostly retained (i.e., from 83.6 ± 24.4% pre- to 90.4 ± 15.2% post-treatment). In control chickens without seeding with blaCMY-2+ E. coli, oral Amp also led to the increase of Proteobacteria, dominated by Klebsiella and Escherichia/Shigella, and a reduction of Firmicutes. Specifically, Enterococcus, Clostridium, etc. were enriched but Lactobacillus was diminished. The fecal resistome including Ampr genes was more abundant in chickens receiving oral Amp than those treated with muscle injection, but the difference was primarily within 1 log. The data illustrated that both drug administration routes and pre-existing gut microbiota have profound impacts on gut microbiome disruption when antibiotic treatment is given. In hosts nurtured in a conventional environment, drug administration route has the most evident impact on gut microbiota rather than the size of the targeted blaCMY-2+ gene pool, possibly due to the pre-existing bacteria that are (i) less susceptible to Amp, and/or (ii) with Ampr- or multidrug resistance-encoding genes other than blaCMY-2+. These results demonstrate the critical interplay among drug administration routes, microbiota seeded through the gastrointestinal tract, AR, gut microbiota disruption, and the rise of common opportunistic pathogens in hosts. The potentially implications in human and animal health are discussed.